2016
DOI: 10.1038/ng.3715
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analyses using electronic health records identify new loci influencing blood pressure variation

Abstract: Longitudinal electronic health records on 99,785 Genetic Epidemiology Research on Adult Health and Aging (GERA) cohort individuals provided 1,342,814 systolic and diastolic blood pressure measurements for a genome-wide association study on long-term average systolic, diastolic, and pulse pressure. We identified 39 novel among 75 significant loci (P≤5×10−8), most replicating in the combined International Consortium for Blood Pressure (ICBP, n=69,396) and UK Biobank (UKB, n=152,081) studies. Combining GERA with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
309
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(328 citation statements)
references
References 60 publications
14
309
1
4
Order By: Relevance
“…rs6749447, rs10474346, rs11564022), or from a gene-age interaction analysis (rs16833934). In addition, we confirmed a further 92 previously reported, but not replicated, loci (Supplementary Table 5)9; together with 274 previously reported loci confirmed, and 535 novel loci identified here, there are 901 BP-associated loci in total.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…rs6749447, rs10474346, rs11564022), or from a gene-age interaction analysis (rs16833934). In addition, we confirmed a further 92 previously reported, but not replicated, loci (Supplementary Table 5)9; together with 274 previously reported loci confirmed, and 535 novel loci identified here, there are 901 BP-associated loci in total.…”
Section: Resultssupporting
confidence: 90%
“…All of the following criteria had to be satisfied for a signal to be reported as a novel signal of association with BP using our one-stage criteria: the sentinel SNP has P < 5 × 10 -9 in the discovery (UKB+ICBP) meta-analysis;the sentinel SNP shows support ( P < 0.01) in the UKB GWAS alone;the sentinel SNP shows support ( P < 0.01) in the ICBP GWAS alone;the sentinel SNP has concordant direction of effect between UKB and ICBP datasets;The sentinel SNP must not be located within any of the 274 previously reported loci described above (Supplementary Table 4) or the recently reported non-replicated loci from Hoffman et al9 (Supplementary Table 23). …”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…By integrating GTEx data with summary statistics from diverse GWAS, we observed that half of complex trait- associated loci co-localize with a GTEx eQTL. GTEx data have already served as a valuable community resource for the identification of the tissue-specific regulatory effects underlying variants associated with human disease phenotypes 5861 .…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] It is now evident that hypertension is a polygenic trait, wherein rare syndromes of hypertension Regulation of Aldosterone Synthesis by Csk…”
mentioning
confidence: 99%